SISTEM INFORMASI STOK PADA PD. KOPI AYAM RASS JAMBI BERBASIS WEB - Megawati, Merti; Mulyati, Sri; -, Aprianto (LP2M Universitas Nurdin Hamzah, 2023)
Trading Company (PD) AYAM RASSâ€ is a company engaged in the production of ground coffee. Currently, the process of processing inventory stock data is still done manually, so it takes a long time and is less accurate. The purpose of this research is to design and build an information system capable of managing stock data or handling files and for operational transactions. This information system is built using the PHP programming language, HTML with MySQL database on XAMPP. The input data needed are incoming goods data, outgoing goods data, stock data, customer data reports. The process carried out is the processing of stock data, the processing of incoming goods and outgoing goods, the processing of calculating the stock, the processing of customer data, the process of making monthly reports, while the output is in the form of incoming goods reports, outgoing goods reports, warehouse goods reports. The expected result of this research is to create a web-based inventory information system that can simplify and speed up the process of delivering inventory information